Access Management in Lightweight IoT: A Comprehensive review of ACE-OAuth framework - Shrestha, Bikesh (My University, 2023)
With the expansion of Internet of Things (IoT), the need for secure and scalable authentication and authorization mechanism for resource-constrained devices is becoming increasingly important. This thesis reviews the authentication and authorization mechanisms in resource-constrained Internet of Things (IoT) environments. The thesis focuses on the ACE-OAuth framework, which is a lightweight and scalable solution for access management in IoT. Traditional access management protocols are not well-suited for the resource-constrained environment of IoT devices. This makes the lightweight devices vulnerable to cyber-attacks and unauthorized access. This thesis explores the security mechanisms and standards, the protocol flow and comparison of ACE-OAuth profiles. It underlines their potential risks involved with the implementation. The thesis delves into the existing and emerging trends technologies of resource-constrained IoT and identifies limitations and potential threats in existing authentication and authorization methods. Furthermore, comparative analysis of ACE profiles demonstrated that the DTLS profile enables constrained servers to effectively handle client authentication and authorization. The OSCORE provides enhanced security and non-repudiation due to the Proof-of-Possession (PoP) mechanism, requiring client to prove the possession of cryptographic key to generate the access token. The key findings in this thesis, including security implications, strengths, and weaknesses for ACE OAuth profiles are covered in-depth. It shows that the ACE-OAuth framework’s strengths lie in its customization capabilities and scalability. This thesis demonstrates the practical applications and benefits of ACE-OAuth framework in diverse IoT deployments through implementation in smart home and factory use cases. Through these discussions, the research advances the application of authentication and authorization mechanisms and provides practical insights into overcoming the challenges in constrained IoT settings.
Keywords: Authentication, authorization, resource-constrained IoT, enhancing, mechanisms, parameters, deployment, framework